Review on multi-functional performance analysis of MXene for thermoelectricity and electromagnetic interference shielding: challenges and future perspectives - A S M Mannafi; Khairul Habib; Taseen Asrafi; Syed Awais Ali (Results in Engineering)
MXenes, a family of two-dimensional (2D) transition metal carbides and nitrides, have emerged as promising candidates due to their exceptional electrical conductivity, tunable surface chemistry, and structural adaptability. However, a comprehensive assessment of their dual functionality in thermoelectric (TE) conversion and EMI shielding remains infrequent. This review critically explores the interplay between the structural and physicochemical properties of MXene-based materials and their influence on TE and EMI shielding performance. Particular focus is given to recent advancements in MXene hybrid architectures that achieve simultaneous improvements in electrical conductivity, Seebeck coefficient, and EMI shielding effectiveness. In addition to performance metrics, the review addresses key considerations such as long-term environmental stability, scalable synthesis and fabrication methods, and material costs to assess real-world applicability. It also identifies the critical parameters governing both thermoelectric efficiency and EMI shielding behavior. By consolidating current knowledge, this review provides a comparative framework and strategic insights for the rational design of next-generation MXene-based multifunctional materials, targeting efficient energy harvesting and robust electromagnetic protection in practical applications.